Practicality of Student Worksheet on Global Warming Generative Learning Model Based on Cognitive Conflict to Facilitate Students’ Problem Solving Ability - Raudatul Jannah; Akmam Akmam; Hufri Hufri; Leni Aziyus Fitri (Physics Learning and Education, 2026)
Physics learning requires supporting teaching materials, especially on the subject of global warming. This subject requires students' problem-solving ability. Preliminary studies show that students' problem-solving ability are still relatively low. One possible alternative to address this issue is to develop a global warming worksheet based on a generative learning model using cognitive conflict to facilitate students' problem-solving ability. The purpose of this study is to determine the validity and practicality of the global warming worksheet using a generative learning model based on cognitive conflict. This research is a development (R&D) that uses the ADDIE development model. The ADDIE development model is one of the systematic learning design models. The object of this study is a global warming worksheet using a generative model based on cognitive conflict. The measurement data used are validity and practicality. The data obtained were analyzed using descriptive statistical techniques. The validity test indicates that the worksheets were valid for use with a score of 0.91 by experts. The practicality test results showed that the worksheets were very practicable for use with a score of 99.22% by practitioners and 88.01% by users. The results of the study concluded that the developed worksheets were valid and very practicable for use in supporting physics learning